Menguak Kemerosotan Moral Gen Z Dalam Film Sajen: Kajian Psikoanalisis Sigmund Freud - Sihombing, M. Sholeh; Mawarni, Cantika; Nia, Nia; Sitompul, Monalisa Senada; Hadawiyah, Andina; Anggreini, Heny (Asosiasi Ide Bahasa Kepri, 2024)
The film Sajen shows a form of moral decandant in Gen Z that still often occurs in their social lives. The acts of bullying, juvenile delinquency, and cyberbullying shown in this film are examples of moral decline that has followed the current young generation. The purpose of this study is to see the implications of bullying on Alanda's personality and mentality as a victim, as well as to see the personality that encourages Bianca to be aggressive as shown in the Sajen film through the analysis of Sigmund Freud's Psychology. The research method used is a qualitative method using several stages, including literature study, data analysis, and data validity. The results of this study found that the conception of id and ego has an effect on the emergence of Alanda's intention to commit suicide while the superego is related to the ego in showing morality to Alanda. Meanwhile, Bianca's id and ego play a role in showing Bianca's personality which encourages her to be aggressive. One of Bianca's aggressive actions encountered in Sajen's film is in the form of bullying several students at school.